2021
DOI: 10.1007/s12144-021-02078-8
|View full text |Cite
|
Sign up to set email alerts
|

The association of WTELS as a master motivator with higher executive functioning and better mental health

Abstract: The goal is to test the validity of the "Will to exist-live and survive (WTELS) as a master motivator that activates executive functions. A sample of 262 adults administered different measures that included WTELS and executive functions. We conducted hierarchical regressions with working memory deficits (WMD) and inhibition deficits (ID) as dependent variables. We entered in the last steps resilience and WTELS as independent variables. We conducted path analysis with WTELS as independent variables and WMD and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…A multisystemic perspective may be appropriate to deal with such complex syndromes (e.g., Bell et al, 2021; Kira, 2002). Some suggested augmenting the cognitive and exposure approaches by adding precognitive metamotivational factors such as stimulating the “will-to exist-live and survive” (WTELS; Kira, Arıcı Özcan, et al, 2020; Kira, Özcan, et al, 2021; Kira, Shuweikh, Kucharska, Al-Huwailah, & Moustafa, 2020; Kira, Ayna, et al, 2021; Kira, Shuwiekh, Kurchaska, Bujold-Bugeaud, 2021; Kira, Shuwiekh, Ashby, et al, 2021; Kira, Shuwiekh, Rice, et al, 2021; Kira et al, 2022). Others recommended addressing identity factors (e.g., Kira & Tummala-Narra, 2014; Kira & Wroble, 2016; Kira, Ashby, et al, 2015; Kira, Omidy, et al, 2015; Kira, Shuwiekh, & Bujold-Bugeaud, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A multisystemic perspective may be appropriate to deal with such complex syndromes (e.g., Bell et al, 2021; Kira, 2002). Some suggested augmenting the cognitive and exposure approaches by adding precognitive metamotivational factors such as stimulating the “will-to exist-live and survive” (WTELS; Kira, Arıcı Özcan, et al, 2020; Kira, Özcan, et al, 2021; Kira, Shuweikh, Kucharska, Al-Huwailah, & Moustafa, 2020; Kira, Ayna, et al, 2021; Kira, Shuwiekh, Kurchaska, Bujold-Bugeaud, 2021; Kira, Shuwiekh, Ashby, et al, 2021; Kira, Shuwiekh, Rice, et al, 2021; Kira et al, 2022). Others recommended addressing identity factors (e.g., Kira & Tummala-Narra, 2014; Kira & Wroble, 2016; Kira, Ashby, et al, 2015; Kira, Omidy, et al, 2015; Kira, Shuwiekh, & Bujold-Bugeaud, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The extreme lowering of status in the hierarchy can yield vicious dynamics that prevent the person from achieving his/her potentials. Examples of such vicious dynamics are lower self-esteem (de Freitas et al, 2018;Kira et al, 2015;Kucharska, 2018) and self-efficacy (de Freitas et al, 2018), internalized inferiority (for meta-analysis see: Gale et al, 2020), stereotype threat (e.g., Inzlicht et al, 2012), and lower will to live and survive (Kira & Shuwiekh, 2021;Kira, Özcan et al, 2021d;Kira, Ayna et al, 2021c). Discrimination comprises microaggressions (e.g., implicit and explicit insults to identity status and exclusion) (Sue & Spanierman, 2020) and macroaggressions such as hate crimes, police brutality, and systemic racism.…”
Section: Identity (Personal and Collective) Trauma Modelmentioning
confidence: 99%
“…Type III is the continuous traumas/stressors with prolonged time scales that may continue through life. Type III traumas have subtypes or variants that fall under the broader umbrella term of type III trauma, varying in III-a) and COVID-19 (type III-e) intersection Kira et al, 2021c;Solomon & Heide, 1999;Terr, 1995). The macro-dynamics of intersection, polyvictimization, accumulation, and proliferation, and the interaction among preidentity, identity, and post-identity stressors and traumas determine their total health, mental health, and cognitive impact from a life-course perspective (e.g., Kira et al, 2012aKira et al, , 2012cKira et al, , 2012dKira et al, , 2014aKira et al, , 2014bKira et al, , 2018aKira et al, , 2019aKira et al, , 2019bKira et al, , 2019dKira et al, , 2020dKira, Barger et al, 2019, 2020.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study found that WTELS, as a master motivator, activates executive functions (working memory and inhibition deficits) and was directly and indirectly associated with lower depression, anxiety, PTSD, and COVID-19 traumatic stress. Its indirect effects were mediated by its effects on lower executive function deficits (Kira, Ayna, et al, 2021). Another study identified two circuit pathways in coping with cumulative adversities in believers and nonbelievers: Interfaith spirituality and WTELS, with WTELS, was the main coping pathway for nonbelievers compared to those who believe in a higher power (Kira, Özcan, et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…stressors and traumatic stressors related to the disturbed life routines, isolation, and family and social life. In addition, grief and mourning of losing to COVID-19 infection and death is another (Kira, Ayna, et al, 2021). COVID-19, with its unprecedented impact, is challenging the individual capacity to cope.…”
Section: Discussionmentioning
confidence: 99%